A degenerate primer MOB typing (DPMT) method to classify gamma-proteobacterial plasmids in clinical and environmental settings. - Andrés Alvarado; M Pilar Garcillán-Barcia; Fernando de la Cruz (PLoS ONE, 2012)
Transmissible plasmids are responsible for the spread of genetic determinants, such as antibiotic resistance or virulence traits, causing a large ecological and epidemiological impact. Transmissible plasmids, either conjugative or mobilizable, have in common the presence of a relaxase gene. Relaxases were previously classified in six protein families according to their phylogeny. Degenerate primers hybridizing to coding sequences of conserved amino acid motifs were designed to amplify related relaxase genes from γ-Proteobacterial plasmids. Specificity and sensitivity of a selected set of 19 primer pairs were first tested using a collection of 33 reference relaxases, representing the diversity of γ-Proteobacterial plasmids. The validated set was then applied to the analysis of two plasmid collections obtained from clinical isolates. The relaxase screening method, which we call "Degenerate Primer MOB Typing" or DPMT, detected not only most known Inc/Rep groups, but also a plethora of plasmids not previously assigned to any Inc group or Rep-type.